A case of acute kidney injury caused by granulomatous tubulointerstitial nephritis associated with sarcoidosis and concomitant presence of anti-glomerular basement membrane antibody - Yoshinori, Kamata; Arata, Azuma; Osamu, Hotta; Kensuke, Joh (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
We encountered a case of granulomatous tubulointerstitial nephritis in a patient with sarcoidosis, who was also found to show an elevated serum titer of anti-glomerular basement membrane (GBM) antibody. The serum creatinine level had been documented to be within normal range 8 months before the first visit. Gallium scintigraphy revealed bilateral kidney uptake, but no uptake in the pulmonary hilum[A1] . No typical findings of sarcoidosis, e.g., bilateral hilar adenopathy, uveitis or elevated serum ACE level were recognized in the early stage. Echocardiography showed basal thinning of the interventricular septum, a specific feature of cardiac sarcoidosis, and hilar lymph node uptake on gallium scintigraphy and anterior uveitis appeared during the disease course. Active tuberculosis, fungal infection, vasculitis and malignancy were clinically excluded. We performed a renal biopsy. Light microscopy revealed non-caseating granulomatous tubulointerstitial nephritis with multinucleated giant cells and normal glomeruli. Inflammatory reaction was seen only within the interstitial tubules. The serum creatinine level had increased to 4.52 mg/dl. The patient was administered methylprednisolone pulse therapy, followed by administration of oral prednisolone. The renal function improved immediately in response to this therapy. Based on the above, we made the final diagnosis of granulomatous tubulointerstitial nephritis associated with sarcoidosis. While the serum titer of anti- GBM antibody was elevated, to our surprise, renal biopsy did not reveal linear anti-GBM antibody staining in this case. Furthermore, interestingly, the serum anti-GBM antibody titer in our patient decreased in parallel with the clinical improvement of sarcoidosis. Severe and progressive renal dysfunction was the most prominent clinical feature without other organ manifestations in our patient, which is a rare occurrence in sarcoidosis.